Steady-State Analysis and Output Voltage Minimization Based Control Strategy for Electric Springs in the Smart Grid with Multiple Renewable Energy Sources - Yun Zou; Michael Z. Q. Chen; Yinlong Hu; Yun Zou (Complexity)
This paper presents a general steady-state analysis and proposes a minimal compensating voltage (MCV) control scheme for the second generation of electric springs (ES-2) in the power system with substantial penetration of intermittent renewable energy sources. For the steady-state analysis, the relationship among the fluctuating part of the supply voltage, the voltage at the point of common-coupling (PCC), and the compensating voltage provided by ES-2 is derived, which implies that the phase angle related to the PCC voltage can be used as a degree of freedom for the control design to obtain a minimal compensating voltage in a given system. Such a fact is utilized in the control design to obtain the reference of PCC voltage by tuning the above-mentioned phase angle. Once the phase angle of the PCC voltage is chosen, the maximal compensating voltage can be estimated based on the fluctuating part of the supply voltage which can be estimated a priori. Such a fact can be used to design suitable electric springs with appropriate compensating capacity to avoid overcapacity. Numerical simulations are conducted to verify the effectiveness of the steady-state analysis and the proposed control scheme for ES-2.